1993
DOI: 10.1093/oxfordjournals.annonc.a058662
|View full text |Cite
|
Sign up to set email alerts
|

High dose chemotherapy followed by autologous hematopoietic rescue in Hodgkin's disease: Long term follow-up in 128 patients

Abstract: Prolonged failure-free survival may be observed following high dose chemotherapy and autologous hematopoietic rescue in patients with Hodgkin's disease. Superior results were seen in patients without extensive prior chemotherapy and in those with a good performance status. Late relapses and deaths from secondary myelodysplastic syndromes mandate prolonged follow-up after autologous transplantation for Hodgkin's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(70 citation statements)
references
References 30 publications
3
64
1
2
Order By: Relevance
“…FI, performed af- ter salvage chemotherapy was initiated and before ASCT, had independent prognostic value for predicting PFS and OS of HL patients. Salvage cytoreductive chemotherapy followed by HDCT/ASCT resulted in 3-year event-free survival (EFS) rates of 50% or greater [4][5][6][7][8][9] in patients with recurrent/refractory HL, with various factors influencing outcome, including length of initial remission, presence of extranodal disease, and B-symptoms. [10][11][12] The most important prognostic factor may be patient remission status before ASCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FI, performed af- ter salvage chemotherapy was initiated and before ASCT, had independent prognostic value for predicting PFS and OS of HL patients. Salvage cytoreductive chemotherapy followed by HDCT/ASCT resulted in 3-year event-free survival (EFS) rates of 50% or greater [4][5][6][7][8][9] in patients with recurrent/refractory HL, with various factors influencing outcome, including length of initial remission, presence of extranodal disease, and B-symptoms. [10][11][12] The most important prognostic factor may be patient remission status before ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Patients not achieving complete remission (CR) at first-line treatment or who experience recurrence after CR are often salvaged with cytoreductive chemotherapy followed by high-dose chemotherapy supported by autologous stem cell transplantation (ASCT), inducing long-term disease-free survival in chemosensitive patients assessed on clinical, radiologic, and pathologic criteria. [4][5][6][7][8][9] Most patients who develop a recurrence after ASCT will die of their disease. Therefore, it is important to identify higher-risk patients so new treatment strategies can be developed.…”
mentioning
confidence: 99%
“…Factors predicting poor outcome in prior studies of autotransplants for relapsed or refractory Hodgkin's disease a Interval from end-of-therapy until relapse Ͻ12 months (34,36,39) у1 extra-nodal disease site at relapse (34,35,39,40) Abnormal ECOG performance status (38,43,46,49,51,52) a Resistant relapse (38,42,47) a B symptoms at relapse (39,48,49) Bulk disease at transplant (33,40,41,44,49,53) Female gender (33) Exposure to many chemotherapeutic regimens prior to transplant (33,35,46,47,51,52) Elevated serum LDH at transplant (50) Relapse in previous radiation field (44) Disseminated lung or marrow disease at relapse (49) a Factors reported specifically in first relapse/second complete remission patients. Numbers in parenthesis refer to study cited.…”
Section: Tablementioning
confidence: 99%
“…Wheeler et al, 38 Reece et al, 43 Horning et al, 49 Bierman et al, 51 and Anderson et al 52 identified abnormal performance status as a predictor for poor outcome. We also corroborated the observations of several noting that resistant relapse heralded an inferior result after transplant.…”
Section: Tablementioning
confidence: 99%
“…In studies of relapsed HD patients, long-term survival rates of 50-65% have been reported using various HDC regimens (Reece et al, 1991;Bierman et al, 1993;Chopra et al, 1993;Goldstone et al, 1993 (Philip et al, 1991(Philip et al, , 1995Salzman et al, 1997). In a recent review (Beard et al, 1998) we considered the role and cost-effectiveness of HDC in the treatment of lymphoma for the Trent Institute Working Group on Acute Purchasing (TIWGAP), a regional body established to consider evidence of clinical and cost-effectiveness for new drugs and interventions.…”
mentioning
confidence: 99%